2014
DOI: 10.1038/ismej.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

Early colonizing Esche richia coli elicits remodeling of rat colonic epithelium shifting toward a new homeostatic state

Abstract: We investigated the effects of early colonizing bacteria on the colonic epithelium. We isolated dominant bacteria, Escherichia coli, Enterococcus faecalis, Lactobacillus intestinalis, Clostridium innocuum and a novel Fusobacterium spp., from the intestinal contents of conventional suckling rats and transferred them in different combinations into germfree (GF) adult rats. Animals were investigated after various times up to 21 days. Proliferative cell markers (Ki67, proliferating cell nuclear antigen, phospho-hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…47 However, whether members of the Peptostreptococcaceae and Micrococcacea families interact with the maturating mucosa and why such specific regional interactions were observed deserve further investigations. The role of Escherischia coli early colonization in gut mucosa modeling has been already studied.…”
Section: Discussionmentioning
confidence: 99%
“…47 However, whether members of the Peptostreptococcaceae and Micrococcacea families interact with the maturating mucosa and why such specific regional interactions were observed deserve further investigations. The role of Escherischia coli early colonization in gut mucosa modeling has been already studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, functional classes such as [K] Transcription and [G] Carbohydrate transport and metabolism, were also retained by NLE treatment (Figure ), although the relationship between these functional changes and anti‐obesity bioactivity has not been characterized . GM can also help strengthen mucosal defence by stimulating epithelial renewal and immune maturation and increasing intestinal impermeability . Consistently, our results revealed that NLE treatment upregulated the expression of occludin, which was greatly reduced by HFD, and the expression of ZO‐1 (Figure ), to protect the gut barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of a particular microbiota has been shown to shape all genuine intestinal functions, including absorptive, protective, and secretory functions (19). The intestine undergoes functional maturation during conventionalization, with a pattern of responsiveness dependent on the kinetics of colonization and the bacteria involved (20)(21)(22)(23)(24)(25)(26)(27). Gnotobiotic rodents represent one of the useful tools for deciphering the complex mechanisms of dietary iron on gut microbiota and health (28).…”
mentioning
confidence: 99%